2023
DOI: 10.1039/d3ee00864a
|View full text |Cite
|
Sign up to set email alerts
|

The impact of electrode conductivity on electrolyte interfacial structuring and its implications on the Na0/+ electrochemical performance

Abstract: The molecular and ionic assemblies at an electrode/liquid electrolyte interface, i.e., electric double layer (EDL), define battery performance by directing the formation of stable interphases. An unstable interphase can hamper...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“… 25 Therefore, the introduction of an additional concept, referred to as the EDL, becomes imperative as it considerably impacts the chemical properties and morphology of the SEI through the arrangement of molecular and ionic assemblies in close proximity to the anode. 115 However, numerous additives merely adsorb onto the ZMA surface to generate a EDL without undergoing subsequent reduction to form an SEI. In response to this issue, Huang et al conducted a comprehensive evaluation of 15 organic additives and identified the pivotal determinant of these additives' protective effectiveness as their capacity to generate an SEI layer.…”
Section: Electrolyte Engineering-induced Protective Mechanismsmentioning
confidence: 99%
“… 25 Therefore, the introduction of an additional concept, referred to as the EDL, becomes imperative as it considerably impacts the chemical properties and morphology of the SEI through the arrangement of molecular and ionic assemblies in close proximity to the anode. 115 However, numerous additives merely adsorb onto the ZMA surface to generate a EDL without undergoing subsequent reduction to form an SEI. In response to this issue, Huang et al conducted a comprehensive evaluation of 15 organic additives and identified the pivotal determinant of these additives' protective effectiveness as their capacity to generate an SEI layer.…”
Section: Electrolyte Engineering-induced Protective Mechanismsmentioning
confidence: 99%